Análise de viabilidade ambiental para implantação de uma usina de reciclagem de resíduos da construção e demolição na cidade de Mossoró-RN - Menescal, Débora Laísy Pereira Estigarriga (Universidade Federal Rural do Semi-Árido, 2019)
The construction sector is a respectable activity in a country's economy because of its high potential to produce jobs and consume raw materials. As a result, the construction industry is therefore a major source of environmental impacts, especially due to the large volume of construction and demolition waste (RCD). In order to mitigate these impacts, Brazil implemented Resolution 307/2002 of CONAMA and Law No. 12,305 / 2010 of the National Policy on Solid Waste (PNRS), for an adequate generation of RCDs. The city of Mossoró-RN has shown a rise in its inhabitants, as a result of this fact the civil construction sector is affected positively, where the demand for new housing and reforms increases, and consequently the index of generation of RCD as well. The present work aimed to analyze the environmental feasibility for the implementation of an RCD Recycling Plant in the city of Mossoró-RN. The information was obtained in the present work through interviews in companies responsible for the collection of RCDs and solid wastes from Mossoró-RN, to bodies such as Institute of Sustainable Development and Environment (IDEMA), Mossoró Advanced Pole and the Secretary of Environment and Urbanism SEMURB) from Mossoró for the environmental feasibility analysis of operation and implementation of the recycling plant, as well as analyzes were carried out in several districts in the city of Mossoró in relation to the RCD's willingness to correlate the environmental impacts resulting from the actions of the final destination of construction waste. The research showed that the city of Mossoró-RN does not have an RCD management plan, as recommended by the current legislation. Most of the companies interviewed are not aware of CONAMA's Resolution 307/2002 and Law 12305/2010, and the ones it has, do not meet the established requirements. Regarding the disposition of the RCD by the population, it was confirmed by photographic records, that all over the city the RCDs are inadequately disposed. Thus, one of the actions of immediate measures aimed at the disciplining of the inadequate RCD provisions in the environment / urban found for the present work would be the implementation and operation of the RCD Recycling Plant, which would result in a great positive impact on the environment environment in the city of Mossoró
Monografia
Keywords: Construção civil sustentável; Licenciamento ambiental; Agregados reciclados; Usina de Reciclagem de resíduos da construção e demolição; ENGENHARIAS::ENGENHARIA CIVIL